Spatio-temporal Analysis of An Invasive Alien Species, Vachellia nilotica, on Rodrigues Island, Mauritius, Using Geographic Information Systems and Remote Sensing Techniques - Sunkur, Reshma; Mauremootoo, John (Indonesian Journal of Earth Sciences, 2024)
Invasive alien species (IAS) constitute a large and growing environmental and socio-economic problem. Tropical islands, one of the richest habitats in the world, are especially vulnerable to invasions because of their island-specific flora and fauna. The aim of this study is thus to assess the viability of monitoring IAS distributions on small tropical islands using Geographic Information Systems (GIS) and remote sensing techniques, focusing on the invasive plant species Vachellia nilotica on the island of Rodrigues as a case study. Freely available satellite images are used to conduct the analysis with resulting classified maps having accuracy levels in the high 70s. The results reveal a significant increase in Vachellia coverage from 2013 to 2023 especially along the coasts while the simulation for 2033 indicates an inward migration from coasts to the central plateau which could have severe repercussions on the native vegetation and human activities. Given the high invasive potential of Vachellia, the present findings can support conservation actions and decision making and even support community participation in managing this IAS. In the broader context, the study demonstrates the potential of GIS and remote sensing as cost-effective tools for monitoring certain invasive plant species.